Use of Expert Consultation in a Complex Case of Neuroleptic Malignant Syndrome Requiring Electroconvulsive Therapy. Issue 6 (November 2016) - WITTENAUER WELSH, JUSTINE; JANJUA, A. UMAIR; GARLOW, STEVEN J.; MCCORMICK, LAURIE; HUSAIN, MUSTAFA M.; MAIXNER, DANIEL F.; WEINER, RICHARD D.; HERMIDA, ADRIANA P.
Abstract : Our team at Emory University Hospital contacted experts at the National Network of Depression Centers (NNDC) for clinical guidance concerning a patient with schizophrenia hospitalized in the intensive care unit with a complex case of prolonged delirium secondary to neuroleptic malignant syndrome (NMS). Through the NNDC, leading psychiatrists across the United States with expertise in electroconvulsive therapy (ECT) provided us with treatment strategies based on experience in our area of concern. This report describes our use of ECT to treat severe NMS in this patient with schizophrenia, utilizing the recommendations made by the NNDC's ECT experts concerning electrode position, number and frequency of treatments, and selection of anesthetic induction agents. This case report highlights the utility of expert consultation in the treatment of rare diseases and provides guidance on how to treat NMS in the intensive care unit setting.